2016
DOI: 10.1039/c6ob00725b
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and in vitro splicing inhibition of desmethyl and carba-derivatives of herboxidiene

Abstract: Herboxidiene is a potent inhibitor of spliceosomes. It exhibited excellent anticancer activity against multiple human cancer cell lines. Herein, we describe an enantioselective synthesis of a desmethyl derivative and the corresponding carba-derivatives of herboxidiene. The synthesis involved Suzuki coupling of vinyl iodide with boronate as the key reaction. For the synthesis of carbo-derivatives, the corresponding optically active cyclohexane-1,3-dicarbonyl derivatives were synthesized using an enantioselectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Authors also studied biological activity of the C6 methyl in addition to the pyran ring oxygen of herboxidiene and they found that, the 6‐desmethyl derivative showed the similar activity as natural herboxidiene, which reveals that the methyl group is not essential for interactions with the SF3B subunit of the spliceosome. But, the corresponding carba‐derivatives showed lower splicing inhibitory activity when compared to the 6‐desmethyl derivative, indicating that the tetrahydropyran ring oxygen is important for activity …”
Section: Chemical Synthesesmentioning
confidence: 97%
See 1 more Smart Citation
“…Authors also studied biological activity of the C6 methyl in addition to the pyran ring oxygen of herboxidiene and they found that, the 6‐desmethyl derivative showed the similar activity as natural herboxidiene, which reveals that the methyl group is not essential for interactions with the SF3B subunit of the spliceosome. But, the corresponding carba‐derivatives showed lower splicing inhibitory activity when compared to the 6‐desmethyl derivative, indicating that the tetrahydropyran ring oxygen is important for activity …”
Section: Chemical Synthesesmentioning
confidence: 97%
“…Another coupling partner 52 was synthesized by cross‐metathesis reaction with olefin 54 and vinyl pinacol boronate. Sidechain fragment 54 was prepared by asymmetric alkylation of iodide compound 55 , which was prepared by using an asymmetric crotylboration of suitable aldehyde …”
Section: Chemical Synthesesmentioning
confidence: 99%
“…C6-Desmethylherboxidiene (87) inhibited splicing in vitro with an IC 50 of 0.35 μM which was comparable to that of herboxidiene (IC 50 :~0.30 μM). [78,79] Replacement of the tetrahydropyrane ring with a cyclohexane generated a carbaderivative of herboxidiene (92). [79] The potency of 92 in in vitro splicing inhibition decreased significantly with an IC 50 of 6 μM, which indicated that a tetrahydopyran ring is important for activity.…”
Section: Sar Of Monopyranesmentioning
confidence: 99%
“…It has been shown that Herboxidiene modulates alternate splicing of the MDM-2 pre-mRNA [ 102 ]. GEX1A inhibits constitutive and alternative splicing by targeting SF3b1, blocking the association of SAP155 in SF3b [ 103 ] and disrupting the transition from A to B complex in the spliceosome assembly pathway [ 104 ].…”
Section: Small Molecules That Modulate Splicing With Potential In mentioning
confidence: 99%